PENERAPAN STRATEGI URBANISME LANSKAP DALAM PLACEMAKING DI WADUK SETIABUDI - Hanjaya, Michael; Ariaji, Priscilla Epifania (Jurusan Arsitektur dan Perencanaan, 2024)
The reservoir in Setiabudi, Jakarta, has the potential to become a meaningful place for the surrounding community. By implementing Landscape Urbanism approaches, we can create spaces that integrate green and blue elements, enhancing residents' care and ownership of the reservoir. The main goal of this project is to transform the reservoir into an attractive and beneficial